Optimization of Medication Regimens in Patients with Type 2 Diabetes and Clinical Atherosclerotic Cardiovascular Disease - Jarred Prudencio; Paige Cajudoy; Donald Waddell (MDPI AG, 2021)
The American Diabetes Association recommends that patients with type II diabetes and atherosclerotic cardiovascular disease be prescribed an SGLT-2 inhibitor or GLP-1 agonist for cardioprotective benefit. This project assessed the use of these medications in this patient population in a rural clinic by measuring prescribing rates of SGLT-2/GLP-1 therapy before and after pharmacist interventions. Of the 60 patients identified at baseline, 39.39% (13/33) managed by a pharmacist were prescribed SGLT-2/GLP-1 therapy compared to the 14.81% (4/27) who had not seen a pharmacist (p = 0.025). Of the 43 patients that were not on SGLT-2/GLP-1 therapy at baseline, 13 were lost to follow-up and 13 had contraindications. For the 17 remaining patients, pharmacists recommended initiating SGLT-2/GLP-1 therapy and were able to successfully initiate therapy for 9 patients (52.94%). Pharmacist interventions improved the prescription rates from a baseline of 36.17% (17/47) to 55.3% (26/47) (p = 0.002), with SGLT-2/GLP-1 therapy contraindicated in 27.66% (13/47) of patients. This suggests that patients managed by a pharmacist have medication regimens that were optimized at a greater rate and pharmacists can have a positive impact on the appropriate medication usage in this population.